Modeling the Performance of Amorphous Silicon in Different Typologies of Curved Building-integrated Photovoltaic Conditions - M. Esmaeili Shayan; G. Najafi; B. Ghobadian; S. Gorjian (Iranica Journal of Energy and Environment, 2022)
Photovoltaic cells are a significant renewable energy source due to their cheap cost and renewability. In both warm sunny and colder and cloudier conditions, a-Si modules outperform c-Si modules on a normalized energy basis. This study investigated 1 m2 of amorphous photovoltaic silicon on curved surfaces. The Taguchi and response surface methods were utilized to expand the model in real terms. Results demonstrated the technology gap in the use of silicon crystal photovoltaics is eliminated. The maximum power in the Taguchi method test is 59.87 W, while the minimum power is 57.84 W when the system is deployed on a flat surface, and the maximum power in the RSM Test is 61.14 W when the system is deployed on a hemispherical surface, and the minimum power is 56.6 W when the system is deployed on a flat surface. The minimal performance was 7.1% on a level surface. The flat surface produced 810 kWh, the cylindrical surface 960 kWh, and the hemisphere 1000 kWh. The NPV at Flat surface is $697.52, with a 34.81%, IRR and an 8.58-year capital return period. Hemisphere and cylindrical surfaces both get $955.18. The investment yield was 39.29% for cylindrical constructions and 40.47% for hemispheres. On the flat surface, doubling fixed investment improved IRR by 21.3%. The cylindrical system increased by 25.59% and the hemisphere by 24.58%. The developed simulation model is empirically evaluated using a MATLAB computer tool; the key findings from the validation procedure are reported in this study.